Proceedings of the 19th ACM International Conference on Multimodal Interaction 2017
DOI: 10.1145/3136755.3136816
|View full text |Cite
|
Sign up to set email alerts
|

Mining a multimodal corpus of doctor’s training for virtual patient’s feedbacks

Abstract: Doctors should be trained not only to perform medical or surgical acts but also to develop competences in communication for their interaction with patients. For instance, the way doctors deliver bad news has a significant impact on the therapeutic process. In order to facilitate the doctors' training to break bad news, we aim at developing a virtual patient ables to interact in a multimodal way with doctors announcing an undesirable event.One of the key elements to create an engaging interaction is the feedbac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Second, to mark that the speaker can take the turn back and continue speaking, and third, to express an attitudinal reaction to the content presented by the speaker, often in combination with verbal feedback. Porhet et al (2017) found that head movements are the most common feedback modality both from doctors toward their patients and vice versa in a medical interaction corpus. The authors also found that a nod from the speaking doctor toward the listening patient is followed by a nod in response from the patient 29% of the time.…”
Section: Feedback In Different Modalitiesmentioning
confidence: 99%
“…Second, to mark that the speaker can take the turn back and continue speaking, and third, to express an attitudinal reaction to the content presented by the speaker, often in combination with verbal feedback. Porhet et al (2017) found that head movements are the most common feedback modality both from doctors toward their patients and vice versa in a medical interaction corpus. The authors also found that a nod from the speaking doctor toward the listening patient is followed by a nod in response from the patient 29% of the time.…”
Section: Feedback In Different Modalitiesmentioning
confidence: 99%
“…Moreover, we also identified sequences of multimodal features (mainly POS tags and gestures) that could be used as backchannel predicting cues [14]. From these sequences, several rules have been extracted for generating backchannels:…”
Section: Backchannels Predictive Featuresmentioning
confidence: 99%
“…Different gestures of both doctors and patients have been annotated: head movements, posture changes, gaze direction, eyebrow expressions, hand gestures, and smiles. More details on the corpus are presented in [13]. Three annotators -paid graduate students in linguistics -coded the corpus, with 5% double-checked for validation (Cohen's Kappa=0.63).…”
Section: From Sequences To Temporal Features Learning 21 Multimodal mentioning
confidence: 99%